Weight Reduction Through a Cognitive Behavioral Therapy Lifestyle Intervention in PCOS: The Primary Outcome of a Randomized Controlled Trial. Issue 11 (23rd September 2020) - Jiskoot, Geranne; Timman, Reinier; Beerthuizen, Annemerle; Dietz de Loos, Alexandra; Busschbach, Jan; Laven, Joop
Abstract : Objective: Long‐term weight loss is important and difficult to achieve for many women with polycystic ovary syndrome (PCOS). Lifestyle interventions (LS) in PCOS have shown moderate short‐term effects. Three‐component LS that combine nutrition advice, exercise, and cognitive behavioral therapy have not been tested in long‐term interventions. Methods: Women ( N  = 183) with PCOS who were trying to conceive and had BMI > 25 kg/m 2 were assigned to 20 group sessions of cognitive behavioral therapy combined with nutrition advice and exercise (LS with or without Short Message Service [SMS] via mobile phone) or care as usual (CAU). Results: More weight loss was observed in LS than in CAU ( P  < 0.001). Adding SMS was even more effective ( P  = 0.017). In CAU, 13 of 60 (21.8%) succeeded in achieving a 5% weight loss, as did 32 of 60 (52.8%) in LS without SMS and 54 of 63 (85.7%) in LS with SMS. The odds of achieving a 5% weight loss were 7.0 ( P  < 0.001) in LS compared with CAU. More than 18 of 60 (29.0%) of the women in CAU gained weight versus 5 of 60 (8.5%) and 2 of 63 (3.1%) in LS without or with SMS, respectively. The overall dropout rate was 116 of 183 (63.4%). Conclusions: A three‐component LS program resulted in reasonable weight loss in women with PCOS. Adding SMS resulted in more weight loss.